Understanding the impact of physical fatigue and postural comfort experienced during motorcycling: A systematic review (2019)
Background: This literature review examines reports on the effects of fatigue and comfort on the motorcycle driving experience and evaluates studies of associated relevant risk factors for musculoskeletal disorders. Methods: This systematic review of literature employed a synthetic approach using best evidence to address the question: “Does fatigue and postural comfort contribute to the development of musculoskeletal conditions and disorders presented by motorcyclists?” The initial search identified 9,024 academic articles published from 1970 to date, in 13 databases. After screening, a total of 35 articles met the criteria and were included. twelve were found to be of high quality, eighteen of medium quality, and five of low quality. Results: In this systematic review, postural and anthropometric factors, as well as techniques and tools for the muscular analysis of motorcyclists were identified. The tools identified were classified into direct assessment techniques (anthropometry, electromyography, dynamometry, vibration evaluation, seat pressure analysis, heart rate and blood pressure, and fatigue of the pupillary muscles) and observational or indirect assessment techniques (self-reports and questionnaires). Most of the reviewed studies (83%) included evidence that physical fatigue and postural discomfort affect the performance and are related to musculoskeletal conditions; 17% (six) of the studies evaluated provided neutral evidence. The lower back was the area of the body most affected by discomfort and fatigue in motorcyclists (63% of the studies), followed by the shoulder and forearm (51% of studies). Other affected areas were the neck, and the buttocks reported by 34 to 43% of the included studies. Conclusion: Our review shows that the different muscles affected due to motorcycle driving and the techniques used for assessment need to be comprehensively evaluated. Thus, proper selection and design of motorcycles is imperative for improving the comfort of motorcyclists. © 2019 Elsevier Ltd